The position of the religious authority in Iraq on the Constituent Assembly elections of 1922-1924 (Journal of the College of Basic Education, 2024)
The research shed light on the issue of the position of the religious authority in Iraq regarding the elections of the Constituent Assembly in the years 1922-1924, starting from the beginnings of those elections, which constituted an urgent necessity for the Iraqi political system under the British Mandate, in terms of the fact that the Council was the first parliamentary council whose primary tasks included the legal establishment of state institutions. Modern Iraqiism, such as approving a constitution for Iraq and approving a law for parliamentary elections, thus consolidating the democratic constitutional system that is compatible with the nature of the declared political system, and on the other hand, ratifying the Iraqi-British Treaty of 1922, which was formulated to regulate the relationship between Iraq and Britain, the state, It was mandated under the League of Nations resolution to impose the mandate system, which was approved at the San Remo Conference in 1920. Its initial position stipulated its agreement to hold these elections in exchange for conditions that the British Relief House and the Iraqi government had to implement before holding those elections, and which revolved around ensuring that national elements were not excluded from the elections. Elections by allowing Iraqi parties and associations to carry out their work while allowing freedom of the press and returning those whom Britain exiled from Iraq after the twentieth revolution, and after the procrastination of the British and the Iraqi government, they issued the terms of reference Religious fatwas prohibited Iraqis from participating in elections, and they had a good response among Muslim clerics of all sects. The matter went beyond the support of some Christian clerics, which gave a national character to the situation. The bodies responsible for holding elections were closed in many cities of Iraq, and thus the elections were postponed, and they were not held. It was carried out only after the harsh and harsh dealings with the religious authorities took place at the end of 1923, so that the council was opened in March 1924